Environmental innovation and ecodesign : certainties and controversies - Debref, Romain (Innovation, entrepreneurship, management series. Smart innovation set, 2018)
"The end of the post-war economic boom was marked by the recognition of the environmental problem with the oil crises of the 1970s and, in 1972, the first major UN conference devoted to the human environment. Successive international meetings have resulted in a context where technical change, innovation and industry have assumed a central place in the creation of a new model of society. Against this consensus, the author demonstrates from economic analysis and wide-ranging examples that the environmental innovation doctrine and ecodesign methods remain fragile and can lead to paradoxical results. The first part of this book exposes the doctrine and origins of environmental innovation and the reasons for its authoritative nature, despite its weaknesses, while the second analyzes the concept of ecodesign. The book draws on an extensive literature review and includes examples from economics, management and engineering. This approach places innovation in a systemic perspective that facilitates our understanding of the relationships between the biosphere and the technosphere."--Page 4 of cover.